Antimicrobial resistance and virulence associated genes in Campylobacter jejuni isolated from chicken in Côte d’Ivoire - Goualié, Bernadette G; Akpa, Eric E; Kakou-N’Gazoa, Solange E; Ouattara, Honoré G; Niamke, Sébastien L; Dosso, Mireille (The Journal of Infection in Developing Countries, 2019)
Introduction: Campylobacter jejuni is one of the major causes of gastroenteritis worldwide of the last century. The aim of this study was to investigate the antibiotics profiles and the virulence gene in C. jejuni strains isolated from chicken in Côte d’Ivoire. Methodology: A total of 336 chicken ceaca samples recovered from market of two municipality of Abidjan were examined by conventional microbiological methods and molecular test using PCR. The antibiotic susceptibility tests of the isolates were determined by disk diffusion method. The presence of virulence genes was examined using simple PCR method. Results: Among of 336 samples, 168 (50%) were positives for C. jejuni. Among the C. jejuni isolates, 159 strains (94.64%) were resistant to one or more antimicrobial agents. The highest percentage of antimicrobial resistance was found for Nalidixic acid (85.33%), Tétracyclin (71.76%) and Ciprofloxacin (55.65%). Moreover, MDR including 3, 4, 5 and 6 antibiotics families was detected in 16.66% of isolates. On the other hand, detection of virulence putative gene shows presence of cadF in 100% of tested strains. In addition, cdtA, cdtB and cdtC genes were detected in 100%; 89.51% and 90.32% respectively of C. jejuniisolates. Conclusion: Because of the key role of broiler chicken in human campylobacteriosis infection, it will important in first time to monitoring using of antibiotics in chicken farms and in second time to verify presence of campylobactériosis in country.